Compact desk: Work From Home (WFH) solution - Raja Abdul Rahman, Raja Intan Suhaylah; Umar, Ronaldi Saleh; Asif, Nayeem; Che Haron, Roziha (Asia International Community of Art & Design (AICAD), 2022)
Compact furniture is a significant element nowadays. In response to the pandemic situation, various spaces in most houses are being utilised. Living rooms, dining halls, bedrooms and even balconies and kitchens are being transformed into workspaces. Working from home and online learning are the main reasons compact furniture is becoming more prevalent in every household. The living and working patterns in a compact space are observed in reference to the emotional design concept. Hence, this paper illustrates the functions of compact furniture design that focuses on Don Norman's viewpoints on the three levels of emotional design by presenting the features of the compact furniture design focusing on visceral, behavioural, and reflective levels.